Meningkatkan Mutu Pembelajaran PAI Perspektif Psikologi Pendidikan - Koesmeiran, Hengki; Rezyika*, Icha; Wulandari, Desi; Asiyah, Asiyah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
In this study using library research methods, namely researching library materials or literature related to research problems by selecting, reading, studying, and researching books or other written sources that are relevant to the research title. The approach used is an analytical descriptive approach. Analytical descriptive (descriptive of analize research), namely the search in the form of facts, the results of one's thought ideas through searching, analyzing research results. This study aims to find out how to improve the quality of PAI learning from the perspective of educational psychology. So the results of this study are whether or not the quality of the learning process is also supported by various factors that support a quality learning process. A quality learning process must be supported by qualified and professional personnel, such as administrators, teachers, counselors, and administration. This is also supported by educational facilities and infrastructure, facilities, media, and adequate learning resources, both in quality and quantity, and sufficient costs, proper management and a supportive environment. Educators, of course, in this case get a value that is worth worship to be accountable for it apart from horizontally, namely vertically to Allah SWT. So that the learning approach to religious education, especially the Islamic religion, which is felt to be very effective and efficient, namely the religious approach, because educators need and must master religious teachings in accordance with the religious corridors that they want to transfer to students and of course this is in accordance with the perspective of educational psychology.